Thesaurus of senses : a tool for writers, teachers, students, and word lovers - Hart, Linda, ....- ([Seattle] : Four Cats Publishing, 2019)
The difference between the almost right word and the right word is the difference between a lightning bug and lightning, Mark Twain once wrote. Throughout history, the timely use of the apt word has held enormous sway, in literature, speeches, and texts. How is it that some words hold such power? One thing we know: great words often engage the senses. Thesaurus of the Senses expands your possibilities to see, hear, touch, taste, and smell to describe the world around you. It collects some of the best English sensory words in one place to enliven your writing and build persuasive descriptions. Unlike ordinary thesauri that contain all manner of words—the mesmerizing as well as the mundane—this thesaurus contains the gems of the literary world. Here writers will find excellent company among the careening, clanging, unflinching, frothy, splendorous, and velvety words that will add depth, color, and spice to their work. The book explores rich facets of each of the five senses including shapes, textures, aromas, colors, facial expressions, speech and utterances, visceral responses, mouthfeel, flavors, and the delightful music of onomatopoeia. Also included are exercises to help writers connect with the senses, along with full word and subject indexes. It's an indispensable reference tool for writers, poets, students, teachers, editors, storytellers, bloggers, communicators, and word lovers alike to add more spark to their writing and expand their sensory vocabulary.
Keywords: English literature